Prediction of fatigue properties of natural rubber based on the descriptions of the cracks population and of the dissipated energy. (May 2017) - Marco, Y.; Huneau, B.; Masquelier, I.; Le Saux, V.; Charrier, P.
Abstract: The goal of this paper is to relate the fatigue lifetime to the energy dissipation and the crack population for a Natural Rubber (NR) compound filled with carbon black. First, the dissipated energy is measured by thermal measurements and its evolution with the local strain is described. Then, the crack population under fatigue loading is investigated thanks to interrupted fatigue tests and SEM measurements. The dependency of the evolution of the crack surface density on the local strain and number of cycles is described. Finally, a fatigue criterion is suggested, starting from the basic assumption of accumulation of dissipated energy along the fatigue cycles. Combining the evolution of the dissipated energy and the crack surface density, the energetic criterion can be written as a simple expression using a single parameter. The predictions obtained with the identified criterion are compared with the results from classic fatigue tests and very close agreement is found.